Effects of ERK/p38 MAPKs signaling pathways on MTA-mediated osteo/odontogenic differentiation of stem cells from apical papilla: a vitro study - Jing Du; Yating Lu; Mengxiao Song; Lin Yang; Junqing Liu; Xinyu Chen; Yue Ma; Yan Wang (BMC, 2020)
Abstract Background Stem cells from apical papilla (SCAP) located in the root apex of immature permanent teeth are a reliable cell source for pulp-dentine complex regeneration. Mineral trioxide aggregate (MTA) is a biocompatible material which has been widely used in endodontic treatments. The aim of this study was to elucidate the regulatory role of MTA in the proliferation and differentiation of SCAP. Methods Cell viability was detected by Cell counting kit-8. Characteristics of SCAP were confirmed by Flow cytometric (FCM) analysis and alizarin red staining. Then, MTA-mediated osteo/odontogenic differentiation of SCAP was investigated by reverse transcription polymerase chain reaction. The effect of MAPKs on MTA-mediated osteo/odontogenic differentiation was evaluated by western blot analysis. Results There was no significant difference in cell viability between the control group and the group with lower concentrations of MTA. However, higher concentrations of MTA could inhibit proliferation of SCAP. It is demonstrated that the ALP activity were enhanced, the mRNA and protein expression of BSP, OCN, DSPP, Runx2 were up-regulated. In addition, phosphorylation proteins of ERK, p38 were activated through western blot analysis. Conclusions MTA at appropriate concentration could enhance osteo/odontogenic differentiation of SCAP by activating p38 and ERK signaling pathways. This study provides a new idea for the clinical application of MTA and the treatment of endodontic diseases.